2011
DOI: 10.1371/journal.pone.0022645
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Serine Protease Inhibitor SERPINB4 Inhibits Granzyme M-Induced Cell Death

Abstract: Granzyme-mediated cell death is the major pathway for cytotoxic lymphocytes to kill virus-infected and tumor cells. In humans, five different granzymes (i.e. GrA, GrB, GrH, GrK, and GrM) are known that all induce cell death. Expression of intracellular serine protease inhibitors (serpins) is one of the mechanisms by which tumor cells evade cytotoxic lymphocyte-mediated killing. Intracellular expression of SERPINB9 by tumor cells renders them resistant to GrB-induced apoptosis. In contrast to GrB, however, no p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…SERPINB9 was reported to be a physiological inhibitor for human GzmB (12), which protects lymphocytes from GzmB-induced injury. A recent study showed that SERPINB4 is an intracellular inhibitor for human GzmM that suppresses GzmM-mediated cell death (13). We showed that SERPINB1 and SERPINB8 resided in YTS cells; however, it is unknown whether they inhibit Gzm.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…SERPINB9 was reported to be a physiological inhibitor for human GzmB (12), which protects lymphocytes from GzmB-induced injury. A recent study showed that SERPINB4 is an intracellular inhibitor for human GzmM that suppresses GzmM-mediated cell death (13). We showed that SERPINB1 and SERPINB8 resided in YTS cells; however, it is unknown whether they inhibit Gzm.…”
Section: Discussionmentioning
confidence: 76%
“…SERPINB9 was identified as an intracellular inhibitor of Gzm B (GzmB) (12). SERPINB4 is an inhibitor of Gzm M (GzmM) and suppresses GzmM-mediated cell death (13). However, no physiological intracellular inhibitors have been defined for human GzmH.…”
mentioning
confidence: 99%
“…The three major extracellular protease inhibitors present in normal lung fluid (a 1 -antitrypsin, elafin, and secretory leukocyte protease inhibitor) do not inhibit GrA or GrB, and GrA is active in bronchoalveolar lavage fluid (20). GrH is inhibited by serpin B1 (89), and GrM is inhibited by serpin B4 (90). Furthermore, GrM is inhibited by a1-antichymotrypsin and a 1 -proteinase inhibitor, although weakly (91).…”
Section: Unresolved Questionsmentioning
confidence: 98%
“…72 In addition, GrM can stimulate LPS/TLR-4-mediated signaling via yet to be identified mechanisms. 90 GrM intracellular functioning can be inhibited in tumor cells by human SERPINB4 92 and mouse SPI-CI. 38 Next to these intracellular effects, GrM has also been found to cleave VWF, and may in that way regulate FVIII levels and coagulation 91 in humans: as mentioned previously, mGrM and hGrM display species-specific substrate specificities.…”
Section: Functionsmentioning
confidence: 99%
“…92 SPI-CI has been initially identified in mouse cytotoxic T lymphocytes 93 and has later been found to inhibit purified rat GrM 38 and -to a lesser extent -hGrM. 94 SPI-CI forms the classical SDS-stable serpin-protease complex with rat GrM, and is expressed by purified murine CD8 þ T cells and even more by murine LAK cells.…”
Section: Inhibitorsmentioning
confidence: 99%